Psychotherapy Research: An Interplay between Inner and Outer and a Succession of Meanings - Gudaitė, Gražina (Journal of analytical psychology, 2019)
Psychotherapy research is a rapidly developing area of study that aims to explore the integration of inner and outer conditions of an individual's experience, the interplay between subjective and objective, as well as between individual and collective. Questions regarding a more integrative view and qualitative research in psychotherapy are discussed in the paper. The author introduces some ideas from the studies on psychotherapy effectiveness that were done at Vilnius University by a group of researchers who work in the ‘Centre for research on the psychodynamics of personality’. Clinical psychologists who hold a doctorate degree or who are in doctoral studies in the Department of Psychology at Vilnius University are members of this research group. The subjective understanding about healing episodes and the development of depth premises were the main tasks of these studies. Among other methods, the researchers used the drawing a picture of a healing moment and telling a psychotherapy story recalled by the client to collect data. Two examples of drawing a picture of a healing moment and one example of telling a therapy story are analyzed in the paper. The themes of subjective experience of renewal in psychotherapy as well as the multiplicity of experience and results in psychotherapy are discussed in the paper with case illustrations. This study showed that drawing a picture opens one more dimension of reflection and that it can be an appropriate tool for developing individual narratives as well. Authoring and re-authoring one's life narrative is accepted as part of a productive therapy as well as discovering one's inner authorship. The ability to follow a succession of meanings, as well as a connection to nature and culture could be one of the ways of actualizing an integrative view in psychotherapy research.